Adsorptive-desorptive performance of Chlorellavulgaris for the removal of vanadium from aqueous solutions. Issue 1 (2nd January 2023) - Shu, Xi; Yu, Ya-qi; Liu, Qing-mei; Yang, Jin-yan
ABSTRACT: Studies on Vanadium (V) adsorption in aqueous systems employing biomaterials friendly to the environment are rare. This study investigated the adsorption performance of the living and non-living Chlorella vulgaris ( C. vulgaris ) for V from aquatic systems. Vanadium inhibited the growth of living C. vulgaris . The results of isothermal equations showed that the non-living C. vulgaris biomass was favourable for V adsorption. At 400 mg L −1 V, 50 mg algae biomass, 40°C, and 0.01 M ionic strength for 24 h, the maximum adsorption capacity reached 94.00 mg g −1 . The results of the kinetic studies indicated that chemisorption dominated the V adsorption process. Analysis on the surface of non-living C. vulgaris biomass revealed that hydroxyl groups, carboxylate groups, amide groups, aromatic carbons, and organic halogenated hydrocarbon groups played crucial roles in V biosorption. Vanadium was bound to the active sites on the surface of C. vulgaris through ion exchange action as opposed to redox reaction. Desorption experiments were conducted by eluting the non-living C. vulgaris biomass with 1 M NaOH solution, and the maximum desorption rate of V reached 98%. The results demonstrate that C. vulgaris is a green and highly effective biosorbent for vanadium removal from aquatic systems.